2016
DOI: 10.17945/kjbt.2016.27.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated Hematopoietic Stem Cell Donor Recruitment of the Korean Red Cross: 20 Years Experience

Abstract: Background: The National unrelated hematopoietic stem cell (HSC) donor program started in 1994. The Korean Red Cross (KRC) has participated in this program from the start as a recruiting organization. Results of 20 years of donor recruitment were analyzed to make suggestions to manage potential donors more effectively and improve retention rate. Methods: Statistics on registration, deregistration, and donation of potential HSC donors registered in the Korean Network for Organ Sharing (KONOS) registry from 1994… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…For the past 20 years, only 58.1% of donation registrants from one Korean HSCD registry agreed to donate when they were requested for an actual donation [24]. This agrees with the reports by Denzen et al [20] and Passweg et al [25] that there is a gap between needs and donation of unrelated HSCT in many developing countries.…”
Section: Discussionsupporting
confidence: 74%
“…For the past 20 years, only 58.1% of donation registrants from one Korean HSCD registry agreed to donate when they were requested for an actual donation [24]. This agrees with the reports by Denzen et al [20] and Passweg et al [25] that there is a gap between needs and donation of unrelated HSCT in many developing countries.…”
Section: Discussionsupporting
confidence: 74%
“…Donor attrition is a challenge that registries around the world face, and is higher among individuals from diverse racial/ethnic groups 9,10,35,71 . Lack of communication from the registry and higher levels of ambivalence are associated with higher attrition, 9,71 and multiple studies have shown that regular communication with donors can reduce attrition 72,73 . Retention programs incorporating Why We Swab stories alongside other resources 67,74 may improve knowledge and attitudes toward donation, as well as mitigate the demographic and psychosocial factors that affect donor attrition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the importance of a universal donor recruitment and management program focused on reducing donation-related insecurities through tailored messages and strategies for each ethnic group is clear. According to a report [6], improving the retention rate of Korea's volunteer donors is a cost-effective method, since 1% improvement has an equivalent effect of recruiting 28,000 new volunteer donors. Maintaining a continued increase in the number of volunteer donors while also strengthening efforts to manage retention rates as a means of increasing actual donation are also important in terms of the efficient use of the national budget [7].…”
Section: Introductionmentioning
confidence: 99%